Microbial Characterization of Azotobacter sp Isolates From West Kalimantan in Nitrogen Fertilizer Efficiency in Maize Plants (Zea mays L.) on Peatlands - Nizari Muhtarom; Marudut Sinambela (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
This study aims to characterize the microbial species Azotobacter sp from peat soil in West Kalimantan, which can bind N, dissolve nutrients P, K and produce indole compounds. This research was carried out in the plant pest and disease laboratory, agronomy laboratory and greenhouse, Faculty of Agriculture, Tanjungpura University, Pontianak. This study used a non-factorial Randomized Block Design (RBD) with four levels of treatment. Inoculation of Azotobacter sp isolates was without inoculation of Azotobacter sp isolate (a0), inoculation of WH.3.2.d (a1) isolate, inoculation of Azotobacter sp isolate WH.2.4 (a2), inoculation of Azotobacter sp WH.3.1.l (a3). The study was carried out from September to November 2021. The results showed that Azotobacter sp inoculation significantly affected the parameters of vigor index, growth synchronously, primary root length, wet weight of normal sprouts, and plant height in the greenhouse. From the bioassay test results on seeds and growth testing for 15 days in a greenhouse, the two best isolates were obtained, namely WH.2.4 and WH.3.1.l isolates.